Neural commitment of embryonic stem cells through the formation of embryoid bodies (EBs) - Liyang, Gao; Abdullah, Syahrilnizam; Rosli, Rozita; Nordin, Norshariza (Penerbit Universiti Sains Malaysia, 2014)
An embryonic stem cell (ESC) is a good tool to generate neurons in vitro and can be used to mimic neural development in vivo. It has been widely used in research to examine the role of cell signalling during neuronal development, test the effects of drugs on neurons, and generate a large population of functional neurons. So far, a number of protocols have been established to promote the differentiation of ESCs, such as direct and indirect differentiation. One of the widely used protocols to generate neurons is through the spontaneous formation of multicellular aggregates known as embryonic bodies (EBs). However, for some, it is not clear why EB protocol could be the protocol of choice. EB also is known to mimic an early embryo; hence, knowing the similarities between EB and an early embryo is essential, particularly the information on the players that promote the formation of EBs or the aggregation of ESCs. This review paper focuses on these issues and discusses further the generation of neural cells from EBs using a well-known protocol, the 4-/4+ protocol.